Sistem Monitoring Kekeruhan Air Berbasis Arduino Pada Tangki Penampungan Air - Imas Sofia Umul Fathin; Endang Retnoningsih; Syahbaniar Rofiah (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2024)
Water is the main human need in daily life. Every house has a storage container (water tank). Water that is stored for a long period of time can change the quality of the water in the water tank. Therefore, the aim of the research is to make it easier to control water in water tanks by using an Arduino-based circuit so that water storage remains clean and does not cause disease. The research uses the Prototype methodology for system development including needs analysis, system design, implementation and system testing. The Arduino-based water turbidity monitoring system is designed with a 16x2 i2c LCD module. The results of research on an Arduino-based water turbidity monitoring system make it easier to control water in water tanks. This system also helps to determine the condition of the water tank, where generally controlling water turbidity and checking water quality is still done manually.